CEO Power, Corporate Governance, Auditors’ Reputation, and its Effects on Corporate Islamic Bonds Rating - Gusni,; Agustriyana, Darwis; Tarmidi, Didi; Butar Butar, Anderson (International Journal of Psychosocial Rehabilitation, 2020)
Islamic bonds, commonly known as "sukuk," are one of the capital market instruments that have come up as one of the important components in the global Islamic financial system and have become an innovative investment instrument for recent years. The purpose of this paper is to investigate the effect of CEO power, corporate governance, auditors reputation, and firm characteristics as control variables (productivity, leverage, and firm size) on the corporate Islamic bond rating listed on the Indonesian stock exchange for the period of 2013-2017. This research uses the ordinal logit regression model to find out variables that have a powerful effect on the corporate Islamic bond rating. Samples were taken from 11 firms that issued Islamic bonds by using the purposive sampling technique. The research finding was denoted that CEO power, board size, and leverage have no effect on the Islamic bond's rating. This result was explained by saying that CEO power is measured by CEO tenure; board size and leverage do not determine the better corporate Islamic bond rating. Meanwhile, auditors reputation, board composition, productivity, and firm size have a positive effect on the corporate Islamic bond rating.